Pencegahan Fraud Dana Desa Melalui Kepatuhan Pelaporan Keuangan dan Sistem Pengendalian Intenal: Studi Kasus di Kecamatan Delanggu - Triawan Hidayat; Heni Susilowati (Pusat Riset dan Inovasi Nasional, 2026)
Transparent and accountable management of village funds is essential for mitigating corruption and fraudulent action that adversely affect the community. This study aims to evaluate the influence of financial reporting compliance and internal control system on fraud prevention in the management of village funds, specifically in the villages of Delanggu District. This study utilised a quantitative technique through a survey approach, collecting data via questionnaires delivered directly to 64 village outhorities using a comprehensive sampel strategy. Data analys is was performed with multiple linear regressions. The results demonstrate that financial reporting comliance and internal control system concurrently and partially exert a positive and significant impact on fraud prevention. This discovery validates that enhancing supervision and executing financial governance are essetial for establishing transparent and accountable village administration. This study indicates the necessity to enhance the competencies of village officials and establish a standardizen internal control system to bolster fraud prevention and promote transparent and accountable management of village funds.